KARAKTERISTIK ORGANOLEPTIK TEPUNG UBI JALAR (IPOMOEA BATATAS) VARIETAS BERBEDA SEBAGAI BAHAN BAKU MP-ASI KUE BANGKIT - Imelda Fitri; Rini Harianti; Hotmauli Hotmauli (STIKes Al-Insyirah Pekanbaru, 2022)
Infant’s complementary feeding innovation by using the local food Ipomoea Batatas with four variants they are orange, purple, yellow and white. Purpose of the research was to determine organoleptic, from four flour variants. Design of the research was experimental study. Data were analyzed using Duncan’s test. The result of the hedonic test showed the average value of panelist’s favorite level on the overall attributes of sweet potato flour range from 3.66 – 4.32. the highest score for favorite is given to purple sweet potatoflour and the lowest is to yellow sweet potato flour. Analysis of variance showed that differences in sweet potato varieties had significant effect (p<0.05). selected sweet potato flour in the organoleptic test was obtained based on the largest average value and the overall attribute was purple sweet potato flour